Assessing Poverty and Unemployment in Sabah: The Role of Mobile Job Matching Platforms in Reducing Economic Disparities - Aliyyatul Muna Binti Ahmad Roslan; Nur Faizah Mohd Pahme; Ahmad Sofiyuddin Mohd Shuib; Nur Hazirah Mohd Fuat (Online Journal for TVET Practitioners, 2025)
Sabah, also called the Negeri di Bawah Bayu, is the second largest state in Malaysia, covering 72,500 square kilometres. Sabah is the world’s third-largest island in northern Borneo (Press Release Re-Discovering Sabah, 2023). The Sulu Sea also encloses the state in the northeast, the Celebes Sea in the east, and the South China Sea in the west (Sabah Government Official Website, n.d.). Despite its vast population, the state has a high poverty rate. In order to achieve the research aim, which is to identify the reasons for the existence of a population with poverty in Sabah. Quantitative research design has been employed as the primary method to achieve the research objective. A set of online surveys has been conducted with 383 respondents from Kota Marudu to identify the poverty population and the reason for poverty in Sabah. Kota Marudu was chosen as the sampling of the research because it was recorded as the poorest city in Sabah (Chan, 2022; Azzeri et al., 2020). Therefore, the researcher also used Google Forms to analyse the data collected from the online survey. As the results revealed, Sabah has a high poverty rate, which is caused by several reasons: foreign immigration, inadequate infrastructure, and rural neglect. Undoubtedly, the unemployment rate has reached its peak figure, which has led users to use the job matching platform on mobile applications to reduce unemployment in Sabah. This study significantly helps to reduce poverty, offers a better standard of living, and influences Sabah’s socioeconomic status.